Linguistique appliquée et traitement automatique des langues - Jacqueline Léon (Recherches en didactique des langues et des cultures, 2015)
This article examines the relationship between applied linguistics and natural language processing at the beginning of their institutionalization in the 1960s. In a comparative study, we attempt to account for differences between traditions. In particular we will try to explain why strong links existed in France, particularly in the Atala association, as well as internationally in the Aila, while, in other pioneering countries such as Britain and the United States, applied linguistics turned towards other areas of interest such as instrumentation language teaching and the statistical analysis of texts. Finally, we show how in-depth reflection on linguistic applications in the Ussr fed the interaction between LA and TAL.